2006
DOI: 10.1210/me.2005-0489
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Liver Gene Expression Is Extensive and Largely Dependent upon Signal Transducer and Activator of Transcription 5b (STAT5b): STAT5b-Dependent Activation of Male Genes and Repression of Female Genes Revealed by Microarray Analysis

Abstract: Sexual dimorphism in mammalian liver contributes to sex differences in physiology, homeostasis, and steroid and foreign compound metabolism. Many sex-dependent liver genes are regulated by sex differences in pituitary GH secretion, with the transcription factor, signal transducer and activator of transcription (STAT5b), proposed to mediate signaling by the pulsatile, male plasma GH profile. Presently, a large-scale gene expression study was conducted using male and female mice, wild type and Stat5b inactivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
272
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(295 citation statements)
references
References 56 publications
20
272
1
2
Order By: Relevance
“…In the present study we have characterized bi-directional crosstalk between STAT5b and HNF4α, which both play important roles in liver gene expression, in particular sex-dependent, GHregulated gene expression, as revealed by the analysis of knockout mouse models [6,12,21]. We also demonstrate that STAT5b enhances HNF4α-dependent gene transcription, while HNF4α is shown to inhibit GH-stimulated STAT5b tyrosine phosphorylation, nuclear translocation and transcriptional activity.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the present study we have characterized bi-directional crosstalk between STAT5b and HNF4α, which both play important roles in liver gene expression, in particular sex-dependent, GHregulated gene expression, as revealed by the analysis of knockout mouse models [6,12,21]. We also demonstrate that STAT5b enhances HNF4α-dependent gene transcription, while HNF4α is shown to inhibit GH-stimulated STAT5b tyrosine phosphorylation, nuclear translocation and transcriptional activity.…”
Section: Discussionmentioning
confidence: 54%
“…The importance of this pathway is evident from the characterization of STAT5b-deficient male mice [19,20], which exhibit impaired body growth from approx. 4 weeks of age and a global loss of sex-dependent liver CYP expression [21].…”
Section: Introductionmentioning
confidence: 98%
“…11 However, it would be simplistic to assume that loss of Stat5 would result in physiological defects that could be explained easily through the deregulation of a limited set of target genes. This study provides evidence that the deletion of Stat5 results in complex molecular and physiological changes that have their roots in part in the aberrant activation of otherwise relatively quiescent signaling pathways (for summary, see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…12 There is extensive overlap between the data from the Stat5b-null mice 11 and the liverspecific Stat5 Ϫ/Ϫ mice reported in this work (see Supplementary Table 1). For example, deregulation of several members of the cytochrome P450 family was concordant in both studies.…”
Section: Molecular Networkmentioning
confidence: 93%
“…The genetic and transcriptional mechanisms regulating differences between the sexes have intensively been investigated in the liver but dimorphic gene expression has also been reported in mouse kidney, blastocysts, lacrimal gland, and brain [2][3][4][5]. A recent microarray analysis of 23,574 transcripts by Yang et al revealed the extent of sexual dimorphism in gene expression to be much greater than previously recognized.…”
Section: Extent Of Global Sexual Dimorphismmentioning
confidence: 99%